Implementation of Simple Additive Weighting (SAW) Method in Decision Support System to Determine the Best University in Medan - Erwinsyah Simanungkalit; Jenny Sari Tarigan; Dewi Comala Sari; Annalisa Sonaria Hasibuan (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Continuing studies to university are a hope for prospective students. However, this is an easy problem, because what needs to be considered in choosing such as, accreditation, lecturers, buildings, laboratory, cost of education, and percentage of alumn and others. By using the Decision Support System, the calculation of all the criteria can determine the best university to assist prospective students in choosing and choosing university. The Decision Support System uses the Simple Additive Weighting (SAW) method. Decision Support Problems are basically for the selection of alternative actions that allow prospective students to choose the university they want and will produce the best decision for prospective students to continue at the best university.